Escapando da rejeição social, ganhando capital total: A complexa experiência psicológica de mutilação genital feminina (MGF) entre os Izzi no sudeste da Nigéria - Olayinka Omigbodun; Tolulope Bella-Awusah; Nkechi Emma-Echiegu; Jibril Abdulmalik; Akinyinka Omigbodun; Marie-Hélène Doucet; Danielle Groleau (BMC, 2022)
Plain Language Summary While the deleterious effects of FGM/C on physical health are well documented, we have little knowledge on the psychological experience of this harmful practice. This study aimed to understand the psychological experience of FGM/C in Izzi communities in Southeast Nigeria where FGM/C was widely practiced. In-depth interviews were completed with 38 women from the same ethnic group to explore the collective psychological experience of FGM/C before, during and after the procedure. Our results found that during adolescence, Izzi girls who had not yet undergone FGM/C reported being subjected to intense stigma, humiliation and rejection by their cut peers. This ongoing psychological suffering led many young women to accept or request to be cut, in order to end their psychological torture. Virtually all women reported experiencing severe distress before, during and after the procedure. Some expressed relief from knowing their psychological torture would end and that they would gain social acceptance and a rise in status from being cut. Newly cut young women also expressed that they looked forward to harassing and stigmatizing uncut ones, therein engaging in a complex behaviour that underscores their severe trauma as well as their newly acquired enhanced social status. Our results suggest that prevention strategies need to involve the whole community to develop preventive pathways in a participatory way that empowers girls and women while preventing the deleterious psychological effects of FGM/C and corresponding stigmatizing behaviour towards the uncut. Results suggest the need to provide psychological support for girls and women of practicing Izzi communities of Southeast Nigeria.